2017
DOI: 10.1038/s41598-017-14223-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics ameliorate lupus-like symptoms in mice

Abstract: Gut microbiota and the immune system interact to maintain tissue homeostasis, but whether this interaction is involved in the pathogenesis of systemic lupus erythematosus (SLE) is unclear. Here we report that oral antibiotics given during active disease removed harmful bacteria from the gut microbiota and attenuated SLE-like disease in lupus-prone mice. Using MRL/lpr mice, we showed that antibiotics given after disease onset ameliorated systemic autoimmunity and kidney histopathology. They decreased IL-17-prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
103
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 62 publications
4
103
4
Order By: Relevance
“…were associated with more severe disease whereas they were reduced as disease is controlled with dexamethasone (Luo et al, 2017). The microbiota of MRL/lpr mice, on the other hand, were described to be depleted of Lactobacillaceae and a mix of Lactobacillus strains improved outcomes in this lupus model (Mu et al, 2017b, 2017a; Zhang et al, 2014). These studies did not include gnotobiotic experiments or define which strain mediates the observed effects, making a causal relationship difficult to establish.…”
Section: Discussionmentioning
confidence: 95%
“…were associated with more severe disease whereas they were reduced as disease is controlled with dexamethasone (Luo et al, 2017). The microbiota of MRL/lpr mice, on the other hand, were described to be depleted of Lactobacillaceae and a mix of Lactobacillus strains improved outcomes in this lupus model (Mu et al, 2017b, 2017a; Zhang et al, 2014). These studies did not include gnotobiotic experiments or define which strain mediates the observed effects, making a causal relationship difficult to establish.…”
Section: Discussionmentioning
confidence: 95%
“…Mu et al . showed that the administration of oral antibiotics in lupus‐prone MRL/lpr mice improve the disease by decreasing inflammatory cytokines (i.e. IL‐17) and increasing IL‐10, a cytokine with anti‐inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite pharmacological drugs and the use of antibiotics that produce a negative impact on gut microbiota, there is a great deal of evidence that autoimmune diseases can be treated with antibiotics. Mu et al [111] showed that the administration of oral antibiotics in lupusprone MRL/lpr mice improve the disease by decreasing inflammatory cytokines (i.e. IL-17) and increasing IL-10, a cytokine with anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, treatments improving lupus symptoms in lupus MRL/lpr mice restored gut colonization of Lactobacillus spp. and decreased that of Lachnospiraceae (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, antibiotic treatment initiated postdisease onset, ameliorated lupus-like symptoms that significantly altered the composition of gut microbiota, and, most notably, increased the relative abundance of Lactobacillus spp. (11). Recently, Mardani et al (12) showed that the administration of the probiotics Lactobacillus delbrueckii or Lactobacillus rhamnosus to a pristane-induced SLE mouse model was able to prevent the initiation or the progression of the SLE disease.…”
mentioning
confidence: 99%